The Effect of Social Support on Stucent's Interest in Joining Futsal Extracurricular Activities in Junior High School - Fathan Aziz Ramadhan; Dini Rosdiani; Yudi Hidayat (Journal of Physical and Outdoor Education, 2026)
This study aims to determine the effect of social support on students' interest in participating in futsal extracurricular activities at Nuruzzaman Junior High School. Social support includes support from parents, peers, and teachers, which is assumed to influence students' desire to actively participate in futsal activities. This study used a quantitative approach with a survey method, and involved 11 respondents selected through a purposive sampling technique. The research instrument was a closed-ended questionnaire that measured the level of social support and students' interest. Data analysis was performed using simple linear regression using SPSS. The results showed a significance value of 0.08 > 0.05, which means there is no statistically significant effect between social support and students' interest in participating in futsal extracurricular activities. However, there is a tendency for a positive relationship between the two variables. This study recommends that schools, teachers, and parents continue to pay attention to social support as an important factor in developing student interest, and encourages further research with a larger sample size.